That’s not how the learning works - the paradox of Reverse Innovation: a qualitative study - Harris,MJ; Weisberger,E; Silver,D; Dadwal,V; Macinko,J (Globalization and Health, 2016)
BackgroundThere are significant differences in the meaning and use of the term ‘Reverse Innovation’ between industry circles, where the term originated, and health policy circles where the term has gained traction. It is often conflated with other popularized terms such as Frugal Innovation, Co-development and Trickle-up Innovation. Compared to its use in the industrial sector, this conceptualization of Reverse Innovation describes a more complex, fragmented process, and one with no particular institution in charge. It follows that the way in which the term ‘Reverse Innovation’, specifically, is understood and used in the healthcare space is worthy of examination.MethodsBetween September and December 2014, we conducted eleven in-depth face-to-face or telephone interviews with key informants from innovation, health and social policy circles, experts in international comparative policy research and leaders in the Reverse Innovation space in the United States. Interviews were open-ended with guiding probes into the barriers and enablers to Reverse Innovation in the US context, specifically also informants' experience and understanding of the term Reverse Innovation. Interviews were recorded, transcribed and analyzed thematically using the process of constant comparison.ResultsWe describe three main themes derived from the interviews. First, ‘Reverse Innovation,’ the term, has marketing currency to convince policy-makers that may be wary of learning from or adopting innovations from unexpected sources, in this case Low-Income Countries. Second, the term can have the opposite effect - by connoting frugality, or innovation arising from necessity as opposed to good leadership, the proposed innovation may be associated with poor quality, undermining potential translation into other contexts. Finally, the term ‘Reverse Innovation’ is a paradox – it breaks down preconceptions of the directionality of knowledge and learning